Electrical, Thermal, Flexural, and EMI-Shielding Properties of Epoxy-Based Polymer Composites Reinforced with RGO/AgRGO Spray-Coated Carbon Fibers - Odabasi, Hulya Kaftelen (Mdpi, 2025)
In this study, 8-ply 3K carbon fiber fabrics were spray-coated with Ag/RGO nanoparticles at varying weight ratios (0, 2.5, and 5 w/w). Composite specimens were fabricated, consisting of an unmodified control sample (neat) and three different variants containing 0.075 w/w% RGO, 0.26 w/w% AgRGO, and 0.45 w/w% AgRGO, respectively. The effects of RGO and AgRGO contents on the electrical conductivity, flexural properties, dynamic mechanical properties, and electromagnetic interference shielding (EMI) performance of these composites were investigated. Additionally, the distribution of RGO and AgRGO on the surfaces and interfaces of carbon fibers was examined using field emission scanning electron microscopy to determine the microstructure-property relationship. The increase in the Ag ratio in the AgRGO filler material in the composite from 2.5 to 5 resulted in an increase in both the through-the-thickness and surface conductivity values by 3.5 times, reaching maximum conductivity values (273 x 10-3 S/m and 256 x 10-3 S/m, respectively). Composites containing filler material with an Ag/RGO weight ratio of 2.5 achieved a total electromagnetic shielding efficiency of 18 dB at the X-band frequency region, without loss in flexural strength, while the maximum total electromagnetic shielding efficiency value of 22.68 dB was obtained when the Ag/RGO weight ratio was 5. With a maximum SET value these composites might be suitable for use in areas that do not require primary load-bearing applications, such as satellite, antenna, and avionics system housings.
Keywords: Ag nanoparticles; reduced graphene oxide; spray coating; carbon fiber composites; thermal properties; electromagnetic interference shielding efficiency